Advances in sarcoma molecular diagnostics. Issue 6 (3rd February 2022) - Wang, Xue Qi; Goytain, Angela; Dickson, Brendan C.; Nielsen, Torsten Owen
Abstract: Sarcomas are cancers of mesenchymal origin with the potential to arise in diverse anatomic locations. With over 80 subtypes, which often demonstrate overlapping morphologies, sarcomas frequently require ancillary testing to enable accurate classification. Pathognomonic driver mutations can often be leveraged for diagnostic purposes and include fusion genes, amplification events, and recurrent point mutations. Until relatively recently, the major clinical molecular diagnostic tests have been karyotyping, fluorescence in situ hybridization, and polymerase chain reaction; however, these techniques have a number of limitations. Recent technological advances have led to the development of more comprehensive assays with higher throughput, thereby replacing the need for a suite of single gene tests. These approaches include next‐generation sequencing, fluorescent bar code hybridization, and DNA methylation profiling, among others. Herein, we review the application of recently developed techniques relevant to the diagnosis of sarcomas, and emerging assays with the potential for future development and clinical implementation.